A streamlined and adaptive approach for accrediting a French education system program by ABET-EAC - Barkaoui, Abdelwahed; Ouldasine, Radouane; Bettaibi, Soufiene; Jamart-Gregoire, Brigitte; Ezbakhe, Ahmed (Frontiers in Education, 2024)
In recent times, there has been a notable increase in the demand for accreditations, driven by their essential role in recognizing diplomas, elevating the quality of higher education, facilitating student mobility, enabling the pursuit of multiple degrees, and influencing university rankings. This surge in demand reflects the evolving landscape of higher education in a world that is becoming progressively interconnected and competitive. This paper presents a comprehensive methodology for accrediting study programs in French higher education institutions worldwide that are seeking the Accreditation Board for Engineering and Technology (ABET) accreditation. ABET accreditation is a globally recognized organism of quality for education programs in engineering, computer science, and related fields. The methodology proposed in this paper focuses on aligning ABET's requirements and standards with the specific context of the French Education System (FES). It provides clear guidelines and practical steps for higher education institutions to effectively navigate the accreditation process. The methodology covers the verification of existing study programs, identification of areas for improvement, implementation of corrective actions, and continuous progress monitoring. It emphasizes the importance of continuous improvement and aligning programs with the Program Educational Objectives (POEs). Concrete examples and best practices are shared to illustrate successful implementation of the methodology developed based on the example of the engineering college programs at our university. The results obtained in this case study demonstrate the applicability and effectiveness of this approach within a specific educational context. The approach presented in this contribution can serve as a model for other countries seeking to adapt ABET accreditation requirements to their own higher education systems, further promoting diversity and openness. This reinforces the credibility of the methodology and paves the way for its use in other institutions and programs that operate within similar systems.